KONVERSI PAKAN, LAJU PERTUMBUHAN, KELANGSUNGAN HIDUP DAN POPULASI BAKTERI BENIH IKAN GABUS (CHANNA STRIATA) YANG DIBERI PAKAN DENGAN PENAMBAHAN PROBIOTIK - Ruli Agustin; Ade Dwi Sasanti; Yulisman . (Universitas Sriwijaya, 2014)
ABSTRACT The aims of this research were to study the effects of probiotics on feed conversion, growth rate, survival rate of snakehead fry, bacterial populations in fish snakehead fry and also to measure the best concentrate of probiotics for growth rate, feed conversion, survival of snakehead fry and bacterial populations on fish snakehead’s intestine. This study use completely randomized design with different levels of probiotic treatments that consisted of six treatments and three replications. The treatments were P0 (without probiotics), P1 (2.5 ml. Kg-1 feed), P2 (5 ml. Kg-1 feed), P3 (7.5 ml. Kg-1 feed), P4 (10 ml. Kg-1 feed) and P5 (12.5 ml. Kg-1 feed).Base on the research of probiotics EM-4 on the fish snakehead fry, the feed conversion value is not significantly affected by giving probiotik. lowest feed conversion value is 1.11 and the highest feed conversion value of 1.55. Growth rate, of the highest growth rate of 3.71 %/day 2.14 %/day is the lowest weight. The highest growth of length is 1.93 %/day and the lowest is 1.74 %/day. Meanwhile, Highest survival value by 40% and the lowest was 13.3%. In the bacterial population, there were addition of bacterial population Lactobacillus sp. and decrease the populations of Aeromonas sp. and Pseudomonas sp. Keywords: probiotics, feed conversion, population bacteria, growth and survival rate